PARASITISMO DE ð˜”ð˜¦ð˜ð˜°ð˜ªð˜¥ð˜°ð˜¨ð˜ºð˜¯ð˜¦ ð˜«ð˜¢ð˜·ð˜¢ð˜¯ð˜ªð˜¤ð˜¢ EM RAÃZES DE ABOBOREIRA (ð˜•ð˜¦ð˜®ð˜¢ð˜µð˜°ð˜¥ð˜¢, ð˜©ð˜¦ð˜µð˜¦ð˜³ð˜°ð˜¥ð˜¦ð˜³ð˜ªð˜¥ð˜¢ð˜¦) - Lordello, Luiz Gonzaga E. (REVISTA DE AGRICULTURA, 2020)
PARASITISMO DE ð˜”ð˜¦ð˜ð˜°ð˜ªð˜¥ð˜°ð˜¨ð˜ºð˜¯ð˜¦ ð˜«ð˜¢ð˜·ð˜¢ð˜¯ð˜ªð˜¤ð˜¢ EM RAÃZES DE ABOBOREIRA (ð˜•ð˜¦ð˜®ð˜¢ð˜µð˜°ð˜¥ð˜¢, ð˜©ð˜¦ð˜µð˜¦ð˜³ð˜°ð˜¥ð˜¦ð˜³ð˜ªð˜¥ð˜¢ð˜¦)